ANALYSIS OF OVERLOADING EFFECT ON JAKARTA-CIKAMPEK TOLL ROAD - (NIM 269 91 007), Sederhananto
Abstract : The section of the Jakarta-bound carriageway of the Jakarta-Cikampek Toll Road between Cikampek and West Karawang was opened to traffic at the beginning of 1991. By 1992 significant pavement deterioration had occured and axle load surveys, deflection surveys and insitu investigations of the pavement materials were carried out. The purposes of the investigation described in this thesis were to analysis the survey data, to check design assumptions and to determine the residual life of the pavement. The period covered in the investigation was from the beginning of 1991 to the end of 1992. Two sections of the carriageway were analysed separately : East Karawang to West Karawang (section 1) and Cikampek to East Karawang (section 2). Annual growth in commercial vehicle traffic from 1991 to 1992 was 8.78 % on section 1 and 6.8 % on section 2. These figures are in reasonably good. agreement with design assumption of 7.5 %. However, actual daily commercial vehicle traffic was considerably higher : daily commercial vehicle traffic on section 1 was approximately 70 % greater than predicted and was 34 % greater on section 2. Analysis of axle load data indicates a Truck Factor (standard axles per commercial vehicle) of 4.01, in contrast to the value of 0.7 assumed for the design. During the 2-year period covered. by the analyse, 15.33 % of the single axles carried by the pavement exceeded the legal limit. These illegal axles contributed 97.75 % of total loading. As a consequence of higher the predicted traffic volume and truck factor and the effect of illegal axles, section 1 has in a 2-year period, carried 67.67 % of the loading estimated for a 20-year design life, section 2 has carried 53.33 %. While loading has been considerably higher than predicted, significant deterioration has nevertheles occurred before the design loading was reached. A deflection analysis using the Bina Marga indicated zero residual life along the entire length of pavement. Evaluation of deflection using the Elmod Program indicated varying amounts of residual life along significant lengths of the pavement.